IL-6 and TNF-α promote metastasis of lung cancer by inducing epithelial-mesenchymal transition - Shang, Guan-Sheng; Liu, Lunxu; Qin, Yi-Wei (Oncology letters, 2017)
The characteristics of cancer cells, such as invasiveness, are affected by the tumor microenvironment. Studies have shown that interleukin (IL)-6 and tumor necrosis factor (TNF)-α regulate the proliferation of lung cancer. However, few studies have focused on the effects of IL-6 and TNF-α on metastasis of lung cancer. The present study was designed to investigate whether IL-6 and TNF-α can promote metastasis of non-small cell lung cancer (NSCLC). Sixty-five tumor and matched adjacent tissue samples from patients with NSCLC and corresponding serum samples were collected. Thirty serum samples from healthy subjects were selected as controls. Real-time PCR and western blot analysis were used to measure IL-6, TNF-α, vimentin, E-cadherin, and N-cadherin expression in tissue samples; ELISA was used to measure IL-6 and TNF-α expression in serum samples. The correlation of serum levels of IL-6 and TNF-α with the clinical stage was analyzed; the correlation of IL-6 and TNF-α levels in serum with these tissues was analyzed; the correlation of serum levels of IL-6 and TNF-α with lymph node metastasis and distant metastasis was analyzed. Expression of IL-6 and TNF-α were significantly increased compared with controls in both serum and tissue; IL-6 and TNF-α levels were positively correlated with lymph node metastasis and distant metastasis; IL-6 and TNF-α levels were negatively correlated with E-cadherin level and were positively correlated with N-cadherin and vimentin levels. In conclusion, IL-6 and TNF-α can induce epithelial-mesenchymal transition, and subsequently promote metastasis of lung cancer. Anti-inflammation should be considered for the treatment of lung cancer.